Triad Leadership Based Service Performance Model mediated by Job Satisfaction and Organizational Commitment - Adriani, Zulfina; Rum, Muhammad; Junaidi, Junaidi; Yacob, Syahmardi (ADPEBI Publisher, 2024)
This research aims to test the mediating effect of job satisfaction and organizational commitment on the influence of Triad leadership on service performance. There were 144 research respondentsOPD employees in the West Tanjung Jabung district government. The research method used is descriptive verification analysis and data analysis using Structural Equation Modeling (SEM) with the help of Amos.18 Software.The research results show that the direct influence of triad leadership on job satisfaction, organizational commitment has a positive and significant effect. The direct influence of job satisfaction, organizational commitment on service performance has a positive and significant effect. Triad leadership directly influences service performance positively and significantly. The indirect effect, namely the mediating effect of job satisfaction, is able to influence triad leadership on service performance. The effect of organizational commitment is able to bridge the influence of triad leadership on service performancein the OPD environment of the West Tanjung Jabung Regency government. The importance of job satisfaction obtained by employees and the organizational commitment that is built can improve service performance which is supported by triad leadership by building the sharing of knowledge, trust and power from a triad leader. Suggestions for leaders with triad behavior to continue to build job satisfaction and organizational commitment, especially affective and normative commitment,